The Distribution of the Pesticides and Polychlorinated Biphenyls in Main Areas of the Barents Sea - Lemenkova, Polina (2015)
Currently there is a high level of the environmental risk in the coastal zones of the Arctic. The basin of the Arctic Ocean not only is a unique geographical region, it also has important environmental and strategic functions. At the same time, the Arctic basin is a kind of geographic buffer zone, a boundary through which a constant flow of chemical substances passes by, including pollutants of various kinds. The paper briefly reports current environmental problems of the region: the degrees of the pollution, the main trends and direction of the pollution by pesticides and PCBs, which serve as indicators of the high risk of the marine environment. В настоящее время существует высокий уровень экологического риска в прибрежной зоне Арктики. Бассейн Северного Ледовитого океана является не только уникальным географическим регионом, но имеет важные экологические и стратегические функции. Одновременно, Арктический бассейн является своего рода зоной географического буфера, границей, через которую проходит постоянный поток химических вществ, в т.ч. загрязнителей. Статья рассматривает современные экологические проблемы региона: уровни, основные тенденции загрязнения пестицидами и ПХБ, индикаторами высокого риска окружающей среды моря. info:eu-repo/semantics/published